Nanocellulose recovery from domestic wastewater. (20th January 2021) - Espíndola, Suellen Pereira; Pronk, Mario; Zlopasa, Jure; Picken, Stephen J.; van Loosdrecht, Mark C.M.
Abstract: Wastewater solids could be an attractive source of secondary raw cellulose, mainly originating from toilet paper. Cellulose can be recovered through sieving of raw wastewater, return sludge, or excess sludge. In particular, a large fraction of cellulose (13–15%) can be found in the excess sludge of the aerobic granular sludge produced by the Nereda® wastewater technology. A cellulose extraction method was developed during this study, allowing the recovery of a pulp with over 86 wt% purity. The wastewater derived cellulose fibres could be an excellent source for production of recovered cellulose nanocrystals (rCNC). Several pre-treatment steps needed in cellulose nanocrystals (CNC) production from wood pulp are already performed in the production of toilet paper. Here, the technical feasibility of such rCNC is studied. As reference materials, microcrystalline cellulose and toilet paper were also used. The rCNC were obtained by acid hydrolysis, with yields of ∼30 wt% (pulp basis). The wastewater-based material was rod-like, with high aspect ratio (10–14), crystallinity (62–68%), and chemical structure similar to commercial CNC. The yield of rCNC per gram of cellulose recovered from the influent was 22%, while for excess sludge cellulose it was less (4%). Bio-nanocomposites of rCNC and alginate were also investigated. At 50 vol% loading of rCNC, there was a 50% relative increase in stiffness (18 GPa) compared to matrix (12 GPa). The characterization of rCNC and positive impact in composite materials confirms a suitable quality of wastewater derived CNC. Ultimately, the nanocellulose is a tangible example that recovery of high-end products from wastewater is possible, in line with a circular economy. Graphical abstract: Image 1 Highlights: A facile method for cellulose recovery and estimation in wastewater was proposed. Nanocellulose (CNC) was obtained from toilet paper and wastewater cellulose. Recovered CNC is similar to commercial CNC (shape, crystallinity, stiffness). Recovered CNC results in high stiffness bio-nanocomposites with alginate.